Spatial and temporal variation of ichthyo-faunal diversity with relation to environmental variables in the Lohandra River of eastern, Nepal (Our Nature, 2022)
The present study aimed to examine space and time variation in fish community structure with relation to environmental variables in the Lohandra River. Fish samples were collected based on different habitat representations from March 2020 to February 2021, covering 12 months.  Fish sampling took place from 6 am to 9 am.  For the fish sampling, two cast nets of different sizes were used, one having a large mesh size of having a mesh size of 1 cm, 5 m diameter, and 5 kg weight and another having 0.5 cm, 3 m diameter, and 2 kg weight, covering 200 to 250m across each station to cover all possible areas. In addition, monofilament gill nets with mesh sizes of 6, 8, and 10 cm were used to capture the fish. In each station, 9-gill nets were left late in the evening (5 pm – 6 pm) and taken out early in the morning (6 am – 7 am) in a sampling distance of 200 - 250m. A total of 1178 specimens representing 72 species belonging to 10 orders and 25 families were documented. An analysis of similarity (ANOSIM) testing for both time (R=-0.25, P>0.05) and space (R=-0.28, P>0.05) showed no significant dissimilarity in fish assemblage structure. Results from the similarity percentage analysis (SIMPER) indicated that the fish species: Cirrhinus reba, Labeo bata, Cirrhinus mrigala, Labeo boga, Puntius sophore, Salmostoma bacaila, Channa orientalis, Chagunius chagunio, Glossogobius giuris, Labeo caeruleus, Barilius bendelisis, Colisa faciatus, Esomus danricus, Salmostoma acinaces, and Chitala chitala. The CCA revealed that of the selected environmental variables, three parameters namely, transparency, water temperature, and water velocity (p